Wearable textile patch antenna: challenges and future directions - Mahfuz, M M Hasan; Islam, Md Rafiqul; Chan, Wang Park; Elsheikh, Elfatih A A; Suliman, F M; Habaebi, Mohamed Hadi; Abdul Malek, Norun; Sakib, Nazmus (IEEE, 2022)
Wearable antennas have grown in popularity in recent years as a result of their appealing features and prospects to actualize lightweight, compact, low-cost and adaptable wireless communications and surroundings. These antennas have to be conformal and made of lightweight materials in a low-profile arrangement when attached to various parts of the human body. Near-body operation of these antennas should be possible without degradation. When these characteristics are taken into account, the layout of wearable antennas become challenging, especially when textile substrates are investigated, high conductivity materials are used during manufacturing procedures and body binding scenarios have an impact on the design's performance. Several of these issues arise in the context of body-worn deployment, despite modest changes in magnitude between implementations. This paper examines the multiple issues and obstacles encountered in the construction of wearable antennas as well as the range of materials used, and the Specific Absorption Rate (SAR) effects employed as well as the bending scheme. An overview of the innovative features and their separate approaches to addressing the difficulties lately raised by work in this field conducted by the scientific community is provided as an appendix.